Recovery of Gentamycin Sulphate from Dilute Solution by Adsorptive Bubble Separation Method - MUKHOPADHYAY, GOUTAM; KHANAM, JASMINA (Asian Journal of Chemistry, 2010)
The aim of this work is to study performance criteria of separation of gentamycin from aqueous solution by controlling of different variables and surfactants in adsorptive bubble separation method. Separation and purification of drug component from a mixture of components, separation of enantiomeric drugs mixture, separation of chemical constituents from plant source and removal of drug components from wastewater is carried out through foam separation method. The result showed that gentamycin sulphate can be easily separated from dilute solution of drug mixture in a short time. The influence of active variables including concentration of surface active agent, pH, superficial gas velocity (SGV) and recovery of drug were investigated. The optimum separation has been set as follow: concentration of surface active agent dioctyl sodium sulfosuccinate (DOSS) (1.0 mM) and sodium lauryl sulphate (SLS) (1.0 mM), pH 5, superficial gas velocity 0.054 cm/s and drug recovery 69.55 and 80.32, respectively. The unique advantage of the present work relative to other reported method is the higher separation efficiency and lowest cost.